2023
DOI: 10.1038/s41598-023-43395-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compact TiO2 interface modification on the crystallinity of perovskite solar cells

Saemi Takahashi,
Satoshi Uchida,
Piyankarage V. V. Jayaweera
et al.

Abstract: The effect of TiO2 interfacial morphology on perovskite crystallinity was investigated by modifying the micro and nanoscale surface roughness of compact TiO2. While surface treatments of the compact TiO2 layer are recognized as effective strategies to enhance the photovoltaic performance of perovskite solar cells, the discussion regarding the crystallinity of perovskite atop TiO2 has been limited. In this study, we explored the impact of micro and nano scale interface morphology on perovskite crystal formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The change of halide doping (Cl, Br, I) Changes the band gap which becomes lower for I. George G.Njema [18] also obtained the same foundations, since it indicated that increasing crystallization degree increases efficiency which is related to the absorption coefficient and conductivity. The same results were found by Saemi Takahashi [19] where improving degree of crystallization increases the efficiency. Similarly, Ningya Ren [20] showed that increase of crystal orientation increases the efficiency.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The change of halide doping (Cl, Br, I) Changes the band gap which becomes lower for I. George G.Njema [18] also obtained the same foundations, since it indicated that increasing crystallization degree increases efficiency which is related to the absorption coefficient and conductivity. The same results were found by Saemi Takahashi [19] where improving degree of crystallization increases the efficiency. Similarly, Ningya Ren [20] showed that increase of crystal orientation increases the efficiency.…”
Section: Resultssupporting
confidence: 84%
“…The research done by Saemi Takahashi [19] studied the effects of TiO2 interfacial morphology on perovskite solar cells by modifying micro and Nano surface roughness on the crystallinity of the perovskite layer. He found significant improvement of the crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the electronic structure of the MAPbI 3 film has been reported to depend on the substrate on which the MAPbI 3 film is coated, including the possibility of a chemical reaction at the interface. , The present results of EA­(1 f ) spectra imply that the morphology of MAPbI 3 at the interface significantly depends on the contacted substrate and on temperature, even when the morphology of the bulk crystal is independent of the substrate on which the MAPbI 3 film is coated. In a recent paper, the importance of interlayer morphology in perovskite crystallization has been emphasized in relation to photovoltaic performance and I–V hysteresis in perovskite solar cells.…”
Section: Resultsmentioning
confidence: 99%
“…But the velocity is related to the frequency the atomic radius and the crystal size according to the relationship. ωa = v 0 (22) Hence one gets the absorption coefficient and the transmission coefficient T to be. ∝ = 2k 2 =1/T (23) where the absorption coefficient takes the form…”
Section: Theoretical Model Based On the String Theorymentioning
confidence: 99%
“…The energy bandwidth is dependent on the halide type (Cl, Br, I) and its concentration. work done by Masha Moradbeigi [22] aims to make perovskite cells commercially available. This is done by using simulation.…”
Section: Introductionmentioning
confidence: 99%